Aplikasi Pembelajaran Algoritma Dasar Interaktif Berbasiskan Computer Assisted Instruction - Yulianto, Budi; Heriyanni, Eileen; Sembiring, Radinal Eliset; Amalia, Rininta; Fridian, Rudy (Bina Nusantara University, 2013)
Book as a learning method is less effective and interactive since it can not deliver motion animation. Thus, a more interactive learning method is needed to have a better learning process. The goal of the research is developing an application that provides easiness for students in learning algorithm by combining computerassited instruction (CAI) and internet technology. On the development phase, the research methodo uses fact finding by a survey to students who are or have been learning algorithm and a literature study, and also waterfall method for software development. The research output is a CAI application for learning algorithminteractively. The developed application is interactive for learning process and able to help students in deepen algorithm topics.